A photostable cationic fluorophore for long-term bioimaging. Issue 46 (17th November 2017) - Wang, Lei; Xia, Qi; Hou, Meirong; Yan, Chenggong; Xu, Yikai; Qu, Jinqing; Liu, Ruiyuan
Abstract : The use of a bright and photostable cationic fluorophore for long-term bioimaging in vitro and in vivo is reported. Abstract : Fluorophores for efficient long-term bioimaging are of great importance to fully understand the cellular and molecular processes of disease. In this study, a bright and photostable cationic fluorophore (PPB ) was successfully developed as a long-term tracer. ThePPB displayed advanced properties such as high fluorescence efficiency, large Stokes shift, low cytotoxicity, and good biocompatibility. Moreover, thePPB exhibited comparable photostability to the commercial cell tracker Qtracker 585. More importantly, thePPB can trace HeLa cells as long as 16 passages in vitro and monitor tumor growth for 27 days in vivo . These remarkable features endow thePPB as an ideal fluorescent probe for long-term bioimaging applications.